1965
DOI: 10.1139/v65-183
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical Transformations of Some 4′-Amino-2-Styrylpyridines and Their Salts

Abstract: 'The photochelllical behavior of 4'-amino-, 4'-dimethylarnino-, 4'-diethylamino-, and 4'-di-n-propylamino-substit~~ted trans-2-styrylpyridine were studied. Ultraviolet irradiation of aqueous solutions of the bishydrochlorides and methiodide-hydrochlorides for moderate periods of time produced mixtures of the corresponding cis and trans isomers. Long irradiation times produced the corresponding dimers in all cases except that of trans-4'-di-n-propylamino-2-styrylpyridine. The cis isomers of the free bases and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1967
1967
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…These results underline how methylation at nitrogen converts these switches from purely photochemical P‐type to thermally reversible T‐type photoswitches. These results are in accordance with the observation that replacing a para ‐methoxy substituent with a para ‐dimethylamino substituent in a trans ‐2‐styrylpyridine methiodide dye, which is a structurally similar compound, even inhibits the E ‐ Z isomerization as a result of the increased single‐bond character of the central alkene bond [47] . For 5 a and 5 b , PSS ratios and quantum yields were determined at lower temperatures, at which the thermal back‐relaxation was sufficiently suppressed.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…These results underline how methylation at nitrogen converts these switches from purely photochemical P‐type to thermally reversible T‐type photoswitches. These results are in accordance with the observation that replacing a para ‐methoxy substituent with a para ‐dimethylamino substituent in a trans ‐2‐styrylpyridine methiodide dye, which is a structurally similar compound, even inhibits the E ‐ Z isomerization as a result of the increased single‐bond character of the central alkene bond [47] . For 5 a and 5 b , PSS ratios and quantum yields were determined at lower temperatures, at which the thermal back‐relaxation was sufficiently suppressed.…”
Section: Resultssupporting
confidence: 91%
“…These results are in accordance with the observation that replacing a para-methoxy substituent with a paradimethylamino substituent in a trans-2-styrylpyridine methiodide dye, which is a structurally similar compound, even inhibits the E-Z isomerization as a result of the increased single-bond character of the central alkene bond. [47] For 5 a and 5 b, PSS ratios and quantum yields were determined at lower temperatures, at which the thermal back-relaxation was sufficiently suppressed. It was found that the quantum yields of both the forward and the back-reactions are very high.…”
Section: Photochemical Propertiesmentioning
confidence: 99%
“…William et al 184 studied the photochemical isomerization (trans-cis) of a series of styryl pyridinium dyes (84) by UV irradiation in aqueous and 50% (v/ v) MeOH-H 2 O solutions. They also observed dimer formation upon long irradiation of the dye solutions.…”
Section: B Cis−trans Isomerization Of Cyaninesmentioning
confidence: 99%
“…These coupling constants indicate the trans forms of the dyes in their ground states. It is known that each of the products can be transformed into the corresponding cis isomer by photolysis of their acidic solutions [19], but the cis styryl dye forms are not stable and readily undergo thermal isomerization to the trans form [19]. In addition, it has been reported that significant differences can be observed between the UVevis spectra of the cis and trans isomers [19].…”
Section: Resultsmentioning
confidence: 99%